Bulbil initiation: a comprehensive review on resources, development, and utilisation, with emphasis on molecular mechanisms, advanced technologies, and future prospects - Shu, Fuxing; Wang, Dongdong; Sarsaiya, Surendra; Jin, Leilei; Liu, Kai; Zhao, Mengru; Wang, Xin; Yao, Zhaoxu; Chen, Guoguang; Chen, Jishuang (Frontiers in Plant Science, 2024)
Bulbil is an important asexual reproductive structure of bulbil plants. It mainly grows in leaf axils, leaf forks, tubers and the upper and near ground ends of flower stems of plants.. They play a significant role in the reproduction of numerous herbaceous plant species by serving as agents of plant propagation, energy reserves, and survival mechanisms in adverse environmental conditions. Despite extensive research on bulbil-plants regarding their resources, development mechanisms, and utilisation, a comprehensive review of bulbil is lacking, hindering progress in exploiting bulbil resources. This paper provides a systematic overview of bulbil research, including bulbil-plant resources, identification of development stages and maturity of bulbils, cellular and molecular mechanisms of bulbil development, factors influencing bulbil development, gene research related to bulbil development, multi-bulbil phenomenon and its significance, medicinal value of bulbils, breeding value of bulbils, and the application of plant tissue culture technology in bulbil production. The application value of the Temporary Immersion Bioreactor System (TIBS) and Terahertz (THz) in bulbil breeding is also discussed, offering a comprehensive blueprint for further bulbil resource development. Additionally, six areas that require attention are proposed: (1) Utilization of modern network technologies, such as plant recognition apps or websites, to collect and identify bulbous plant resources efficiently and extensively; (2) Further research on cell and tissue structures that influence bulb cell development; (3) Investigation of the network regulatory relationship between genes, proteins, metabolites, and epigenetics in bulbil development; (4) Exploration of the potential utilization value of multiple sprouts, including medicinal, ecological, and horticultural applications; (5) Innovation and optimization of the plant tissue culture system for bulbils; (6) Comprehensive application research of TIBS for large-scale expansion of bulbil production; (7) To find out the common share genetics between bulbils and flowers.